Penanaman Nilai Norma Sosial dalam Menghadapi Westernisasi di Kehidupan Modern - Surya Arrahman; Moch. Iqbal (Al-Balagh : Jurnal Komunikasi Islam, 2023)
In the era of globalization has brought significant changes in various aspects of life that have had a devastating impact on the life of social communities, namely the influence of western culture (westernization). This research aims to as a reflection of society in order to inculcate social norms in modern life in the face of westernization Using the study of literature. Data collection used with Library data collection, As for the sources used come from books that serve as references related to research. The results of this study show that: (1) The need for human beings to instill the value of social norms in the life of society in the face of the influence of western culture. It aims for the Society to always be wise to the influx of western culture. It is hoped that this research will allow the Society to give priority to social interests, lead a harmonious life, and maintain social balance.